1992
DOI: 10.1002/jcp.1041520216
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator regulation in osteoblasts: Parathyroid hormone inhibition of type‐1 plasminogen activator inhibitor and its mRNA

Abstract: In order to determine the mechanism by which parathyroid hormone (PTH) stimulates plasminogen activator (PA) activity in rat osteoblasts, we investigated the effect of human PTH(1-34) [hPTH(1-34)] on the synthesis of mRNAs for tissue-type PA (tPA), urokinase-type PA (uPA), and PA inhibitor-1 (PAI-1), and on release of PA activity and PAI-1 protein in both normal rat calvarial osteoblasts and UMR 106-01 osteogenic sarcoma cells. hPTH(1-34) (0.25-25 nM) decreased PAI-1 mRNA and protein, and increased PA activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 54 publications
3
20
1
Order By: Relevance
“…With regard to a possible involvement of serine proteinases in bone turnover, plasminogen has been shown to be present in extracellular matrices (Knudsen et al 1986). Furthermore, osteoblasts produce PAs in response to agents that promote bone resorption (Fukumoto et al 1992, Allan & Martin 1995 and most recently it has been suggested that serine proteinases are involved in the degradation of non-collagenous proteins of bone (Daci et al 1999). Although these results support the notion that the PA/plasmin system might be involved in bone resorption, results from other studies suggest a limited role (Leloup et al 1994(Leloup et al , 1996.…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…With regard to a possible involvement of serine proteinases in bone turnover, plasminogen has been shown to be present in extracellular matrices (Knudsen et al 1986). Furthermore, osteoblasts produce PAs in response to agents that promote bone resorption (Fukumoto et al 1992, Allan & Martin 1995 and most recently it has been suggested that serine proteinases are involved in the degradation of non-collagenous proteins of bone (Daci et al 1999). Although these results support the notion that the PA/plasmin system might be involved in bone resorption, results from other studies suggest a limited role (Leloup et al 1994(Leloup et al , 1996.…”
Section: Introductioncontrasting
confidence: 56%
“…RT-PCR analysis also revealed expression of the serine proteinase inhibitors, PAI-1 and PN-1, in primary mouse osteoblasts. Previous studies have demonstrated that PAI-1 mRNA is decreased in rat osteoblasts by PTH and increased by treatment with transforming growth factor-(TGF-) (Allan et al 1991, Fukumoto et al 1992 thus highlighting the importance of PAI-1 in regulating the PA/plasmin system in rat osteoblasts. Allan and Martin (1995) demonstrated that expression of PAI-2 and PN-1 in rat calvarial osteoblasts was not modulated by prostaglandin E 2 whereas PAI-1 was modulated in a biphasic manner.…”
Section: Discussionmentioning
confidence: 99%
“…The cyclic nucleotide regulation of PAI-1 mRNA accumulation, first observed in HTC cells (8), has also been demonstrated in rat testicular peritubular cells (58), astrocytes (59) and osteoblasts (60), mink lung epithelial cells (61), human fibrosarcoma cells (62), umbilical vein endothelial cells (63), and synovial cells (64). Our previous experiments have shown that in rat HTC cells, whereas transcriptional regulation plays a role in the cA-induced decrease in PAI-1, the major effect is on message stability.…”
Section: Figmentioning
confidence: 76%
“…6D shows that, in addition to E4BP4, PTH induces C/EBP␤ binding to EBPRE. PTH inhibits transcription of osteoblastic genes, including both primary (19) and late response genes (20,42,43). The catabolic effects of continuous PTH treatment appear to be associated with decreased expression of many of the genes involved in bone formation and increased expression of genes involved in bone resorption (10).…”
Section: Fig 6 E4bp4 Protein Is Part Of the Pth-induced Binding To mentioning
confidence: 99%